Mastering Your Entrepreneurial Journey From Vision to Venture - Kuckertz, Andreas; Leicht, Thomas; Scheu, Maximilian; da Silva Wagner, Indra; Ebersberger, Bernd; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
Entrepreneurship is a powerful force for change and innovation; you can be a part of it. This open access book is your key to unlocking your potential as an entrepreneur and impacting the world through your actions. Written by experienced startup guides and backed by rigorous academic research, this book takes you through the essential steps along your entrepreneurial journey. This unique mix of theory and practical advice you can apply equips you to master your entrepreneurial journey. From developing your idea to validating it and creating real-world impact, the authors provide you with the tools, methods, and heuristics you need to succeed. Whether you're just starting or looking to take your entrepreneurial skills to the next level, this book is your ultimate guide. With its practical, actionable advice and real-world examples, it is the perfect companion for anyone who wants to make a difference and leave their mark on the world. So what are you waiting for? Start your entrepreneurial journey today!
Introduction to Mastering Your Entrepreneurial Journey -- Demystifying Entrepreneurship: What It Is and What It Is Not -- Navigating the Entrepreneurial Unknown: Benefiting from Unexpected Outcomes -- Targeting the Right Problem With Your Start-Up: Uncovering Validation Techniques -- From Concept to Creation: Mastering Entrepreneurial Prototyping and Prduct Development -- Architecture of the Venture: Understanding Business Modeling -- Pitch Perfect: Impressing Your Audience As an Entrepreneur -- Onwards and Upwards: Hacking Entrepreneurial Growth -- Building Bridges: Leveraging Your Network for Entrepreneurial Success -- Embracing the Entrepreneurial Challenge: Learning from Failures and Setbacks.
Keywords: New business enterprises; Venture capital; Technological innovations; Strategic planning; Leadership; Start-Ups and Venture Capital; Innovation and Technology Management; Business Strategy and Leadership